Elemental content of propolis samples from Pest, Zala and Bács-Kiskun county (Hungary) - Soós, Áron; Reichenbach, Réka; Várallyay, Szilvia; Bódi, Éva; Molnár, Szabolcs; Kovács, Béla (Acta Agraria Debreceniensis, 2017)
The elemental content of 61 raw propolis samples from Pest, Zala and Bács-Kiskun county (Hungary) were analyzed by ICP-OES. The content of Al, B, Ca, Cu, Fe, K, Mg, Mn, Na, P, S, Sr and Zn were measured in the samples. Median is higher than mean in all cases based on the summarized results. It can be explained by the outliers, moreover it has a non-normal distribution. The concentrations are in an extremely wide range, the ratio of the maximum and minimum is under 10 in case of six elements, between 10 and 35.1 in the case of other six elements,and more than 300 in case of Zn. Significant differences are between counties only in the case of B, K and P based on ANOVA. Other elements have no significant differences. The following order can be set up based on the mean concentrations and the wide ranges: K≥Ca>P≥S≥Fe≥Mg≥Al>Zn≥Na>Mn≥B>Cu≥Sr. Moreover it can be established, that the measured concentrations are near the same or in some cases lower than in other publications.